Addressing the Challenges Facing University Instructors in Test Construction Practices in Tanzania - Rubeba, Asia (Educational Challenges, 2024)
This study examined how instructors implement tests in their teaching and learning process and address the challenges facing them during practising test. Methodology. Three universities were chosen. The study was informed by transcendental phenomenological designs. Purposive sampling obtained responses from 48 key informants. Interviews, observations, and documentary analysis were used concurrently to gather data. The data were analysed thematically. Ethical issues were addressed.Results. The analysis revealed that university instructors face multiple challenges, including a large number of students; a lack of manpower/instructors, resources, training on test construction and internal moderation commitment; and a heavy teaching load.The study concludes that assessment is crucial for improving the teaching and learning process and thus determining its quality. Issues that should be addressed include mandatory workshops and seminars for instructors who have not undergone teacher education. Universities should ensure that sufficient human and material resources are available to strengthen assessment efforts aimed at improving teaching and learning.
Keywords: Test; Test Construction Practices; University Instructors; Teaching and Learning; Assessment